Pre-Service Teachers’ Internet Usage a Function of Demographic Factors: The Case of a Nigerian College of Education - Bede Blaise Chukwunyere Onwuagboke; Termit Kaur Ranjit Singh; Fong Soon Fook (Intelektual Pustaka Media Utama, 2014)
With the overreaching acceptance of ICT in education and access to Internet occasioned by advancement in technology, this paper investigates pre-service teachers’ use of Internet in a college of education. The study was a descriptive survey. Data was collected using a researcher designed instrument tagged “Student Internet Use Scale” (SIUS). The population comprised of all NCE pre-service teachers in Alvan Ikoku Federal College of Education Owerri Nigeria. Findings show that mobile phones remains the most widely used mode of internet access with social networking, searching for information on school assignments, chatting forming the major reasons why they surf the net. Social networking is the major purpose for Internet use by female pre-service teachers while school related activities are of priority to males. The difference in purpose of internet use according to gender is however not statistically significant; similarly, there is no statically significant difference between male and female pre-service teachers in the frequency of Internet usage. The result has far reaching implication for provision and use of Internet facilities to enhance teaching and learning in the College and colleges of education in Nigeria.